Waspadai dan Cegah Pneumonia dan Diare di Masa Pandemi Covid-19 - Deborah Siregar; Martina Pakpahan; Peggy Sara Tahulending; Evanny Indah Manurung; Yenni Ferawati Sitanggang; Marisa Junianti Manik (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The leading causes of death in children vary according to age. Children under five years are vulnerable to infectious diseases such as malaria, pneumonia, diarrhea, HIV, and tuberculosis. Pneumonia is a contagious infectious disease and the most significant cause of death in children under five. Diarrhea is the second leading cause of death in children under five. Diarrhea is the leading cause of malnutrition in children under five. Indonesia is included in the top ten countries with the highest number of deaths in children under five years in 2019. This activity aims to increase knowledge of the community, especially mothers, about pneumonia and diarrhea. The method used was a virtual seminar. The webinar was held on May 7, 2021, using a zoom meeting with 87 participants. The majority of participants had never had pneumonia (98.8%). And the number of participants who had experienced diarrhea was 64 participants (80%). The results showed an increase in knowledge after attending the virtual seminar. The average (mean) knowledge score increased by 1.97. The majority of participants gave excellent marks on activities related to the topic/theme of the event, speakers, audiovisual quality, and question and answer sessions.